2008
DOI: 10.3390/s8106507
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Laser Cleaning of Artworks

Abstract: The main tasks of conservators of artworks and monuments are the estimation and analysis of damages (present condition), object conservation (cleaning process), and the protection of an object against further degradation. One of the physical methods that is becoming more and more popular for dirt removal is the laser cleaning method. This method is non-contact, selective, local, controlled, self-limiting, gives immediate feedback and preserves even the gentlest of relief - the trace of a paintbrush. Paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…During the laser ablation of material, measurements performed by the laser interferometry technique demonstrate that ablation induced high pressure on the surfaces of analyzed samples, which can provoke the appearance of delocalized defects formation [14].…”
Section: Laser Irradiationmentioning
confidence: 99%
“…During the laser ablation of material, measurements performed by the laser interferometry technique demonstrate that ablation induced high pressure on the surfaces of analyzed samples, which can provoke the appearance of delocalized defects formation [14].…”
Section: Laser Irradiationmentioning
confidence: 99%
“…The laser cleaning systems contributed to the increasing applications of lasers in conservation, particularly during recent ten to fifteen years [111]. The laser cleaning technique utilizes intense laser radiation to selectively contaminants removal from a solid surface while leaving the underlying substrate largely unaffected [109][110][111]. The technique exploits differences in the optical and thermal properties of the underlying substrate and the contaminant layer as well as the ability of precise control material heating depths and removal rates by controlling laser beam parameters such as pulse time (or scan rate), wavelength, and fluence (or intensity).…”
Section: Laser Cleaningmentioning
confidence: 99%
“…The laser cleaning systems contributed to the increasing applications of lasers in conservation, particularly during recent ten to fifteen years [111]. The laser cleaning technique utilizes intense laser radiation to selectively contaminants removal from a solid surface while leaving the underlying substrate largely unaffected [109][110][111].…”
Section: Laser Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued on next page well-established laser cleaning of stones, 7 in which dark crust ablation from white stone is self-terminated, varnish ablation requires an effective way to monitor the remaining lacquer layer's thickness. We have found that OCT can be used for both realtime monitoring and post-process inspection.…”
mentioning
confidence: 99%